PERAN TOKOH AGAMA DALAM PEMBINAAN KEGIATAN KEAGAMAAN DI MASYARAKAT DESA MUNGKUR BALAI KELURAHAN JANGKUNG RT. 012 KECAMATAN TANJUNG KABUPATEN TABALONG - Pahrurraji Pahrurraji (ADISAM PUBLISHER, 2024)
This research starts from the idea that a religious figure is someone who is used as a role model in various aspects of life, especially regarding religion. His active role is very much needed in a society with the responsibility to shape the quality of the community's religious awareness which is carried out through coaching religious activities as an effort to guide and direct the community so that understand the teachings of Islam properly and correctly in life. This research aims to find out the role of religious figures and supporting and inhibiting factors in fostering religious activities in Mungkur Village, Balai Kelurahan Jangkung Rt. 012 Tanjung District, Tabalong Regency. This research is field research (Field Research) with a qualitative descriptive approach that emphasizes the depth of information obtained through interviews, observation and documentation. In collecting data for this research, the key informants were 2 religious figures and 6 community members as supporting informants. With the research object regarding the role of religious figures in fostering religious activities. The results of this research show that religious figures have carried out their roles very well and carried out religious guidance through religious preaching activities in mosques and at home which serve as assemblies as an effort to provide religious guidance to the community so as to create an environment that has good religious awareness as well. Religious figures are able to devote themselves to the knowledge they possess so that they are able to become role models in everyday life in society.